Penerapan Perawatan Payudara pada Pasien Post Natal Care (PNC) terhadap Keberhasilan Menyusui - Ani Lestari; Lena Atoy; Taamu Taamu (Health Information : Jurnal Penelitian, 2019)
Post Natal Care starts from the first 2 hours after the birth of the placenta until 6 weeks / 42 days after that. During the puerperium, the mother will experience physiological changes. Changes occur in the reproductive system. Changes in the reproductive system include breast (mamae), uterine involutio, discharge of lochia, changes in the endometrium, cervix, vulva and vagina, and in the perineum. Data shows that the number of post-partum mothers in 2015 was 589 (64%), in 2016 the number of post-partum mothers was 931 (65%), in 2017 there were 1,230 people (67%), in 2018 as many as 804 people. This case study aims to determine the success of breast care implementation on the success of maternal breastfeeding in Post Natal Care (PNC) patients. The design of this case study is to use a descriptive research design with the application of case studies with case study subjects using one patient according to predetermined inclusion and exclusion criteria. The data were obtained by direct assessment and interviews with patients and documents at the hospital. The results of the case study found that the application of breast care was effective in increasing the volume of milk produced. The hospital is expected to add and develop existing knowledge and improve the quality of health services, especially for the implementation of breast care for postpartum mothers with breast and breastfeeding problems.